Pengaruh Effective Inoculant Promi Dan Em4 Terhadap Laju Dekomposisi Dan Kualitas Kompos Dari Sampah Kota Ambon - M. C Manuputty; Agustinus Jacob; Johanis P. Johanis P (Agrologia, 2012)
Solid waste management is an old problem in urban areas.  High population growth rates have caused the increasing amount of wastes generated. One of the efforts to solve the problem is to recycle the organic wastes by composting. The purpose of this research was to find out the influence of effective inoculants PROMI and EM4 on decomposition rate and compost quality from municipal waste in Ambon. This research used a Completely Randomized Design (CRD) in single factor experiment using 2 effective inoculants, i.e. PROMI (no Promi = P0, 24 gr Promi/10 kg organic waste = P1, 48 gr Promi/10 kg organic waste = P2) and EM4 (no EM4 = E0, 150 ml EM4/10 kg organic waste = E1, 300 ml EM4/10 kg organic waste = E2). The treatments consisted of the 2 types of inoculants with 3 dosages of each, and 3 replications. The result showed that the addition of effective inoculant EM4 with a dosage of 300 ml per 10 kg organic waste (E2) was more effective compared to the other treatments in accelerating the decomposition rate in 28 days. This was supported by decomposition rate indicators, such as compost physical characteristics, C/N ratio (11.56), and the increased compost quality, such as pH (8.03), Nitrogen (2.91%), Phosphorus (141.33 mg per 100g P2O5), Potassium (553.67 mg per100g K2O). This compost was in accordance to Indonesia National Standard (INS) or Standar Nasional Indonesia (SNI) of organic manure No. 19-7030-2004.